(untitled) (UUM Journal of Legal Studies, 2023)
In state atheism, the issue of secularism is frequently deemed a matter not of “separating religion from the state”, but “separating religion from society” or “rejecting religion from society”. Case studies help in effectively evaluating the extent to which this philosophy can be realized. In this regard, the present article is about a case study on the construction of the secular state in contemporary socialist Vietnamese society. The article is mainly based on the provisions of Vietnam’s legal documents on belief and religion. Analyses of Vietnamese, Russian, and Western scholars on the atheistic state and the secular state have been duly conducted. In addition, the placement of state-religious relations within the cultural framework has created opportunities for studying, visualizing, and illustrating the secular state in its various aspects and in a detailed manner. The author has adopted socio-cultural approaches, which employs logical, historical and legal research methods to analyse, synthesize, compare and clarify the following three issues: (1) the formation and transformation of the secular state in Vietnam; (2) the relationship between the atheistic state and the secular state in Vietnam; and (3) solutions to the problems posed by state secularism in the country. The results indicate that from its establishment in 1945 to the present day, the socialist state in Vietnam has issued legal documents aimed at building a “cooperation” model of a secular state. The model faced certain challenges from 1960 to 1980 due to the influence of other socialist countries, but since the 1986 reform of Vietnam it has increasingly evolved characteristics of a “cooperation” model, which has contributed remarkably in resolving the issue of conflict between the atheist state and the secular state. The harmony between the two types of state, the secular and the atheistic in Vietnam is related to the traditional and cultural elements of Vietnamese society. The cooperation model of a secular state is regarded as the key to building state-religious relations in Vietnam, while a culture of tolerance is fundamental to its construction.